(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the rate of hospital-acquired infections (HAIs) and associated factors at Binh Tan Hospital in 2022. Subjects and Methods: A cross-sectional study was conducted on 424 inpatients across eight clinical departments at Binh Tan Hospital between June and December 2022 (patients hospitalized for ≥2 days). Data were collected via electronic medical records and clinical examinations; HAIs were diagnosed according to Decision 3916/QĐ-BYT. Data were analyzed using Stata 20.0 software, employing Chi-square or Fisher’s exact tests, with statistical significance set at p<0.05. Results: There were 18 cases of HAI, representing a rate of 4.3%. Surgical site infections accounted for the highest proportion (66.7%), followed by respiratory tract infections, urinary tract infections, and bloodstream infections. Associations were found between HAIs and surgical status, length of hospital stay, and the number of procedures performed on patients. Conclusion: The HAI rate at the hospital was 4.3% (18 cases), with surgical site infections constituting the majority (66.7%). Based on these findings, the hospital needs to prioritize and implement interventions to reduce HAI rates, with a specific focus on addressing surgical site infections occurring during and after surgery.